Utilizing TRIPS flexibilities for public health protection through south-south regional frameworks - Musungu, Sisule F.; Villanueva, Susan; Blasetti, Roxana; South Centre (Independent Commission of the South on Development Issues). (Geneva South Centre, 2004)
"This study provides the conceptual as well as a strategic basis for further thinking and decision-making on how effectively to use TRIPS [Trade-Related Aspects of Intellectual Property Rights] flexibilities for public health purposes through regional South-South mechanisms and cooperation. The study should, however, not be seen as the A to Z of regional approaches to the use of TRIPS flexibilities, but rather as a first step. Critical issues with a regional dimension that need to be further explored through empirical research and discussions are identified and explored."--Executive summary.
Abbreviations -- Executive summary -- I. Introduction -- II. Intellectual property and access to essential medicines in developing countries -- III. Constraints on national efforts to implement TRIPS flexibilities for public health purposes -- IV. Overcoming constraints in the use of TRIPS flexibilities through south-south regional frameworks -- V. Conclusions and recommendations -- Bibliography.
"April 2004."
Keywords: Agreement on Trade-Related Aspects of Intellectual Property Rights -- (1994).; Drugs -- Law and legislation -- Developing countries; Patent laws and legislation -- Developing countries; Public health -- Developing countries